Epigenetically maintained SW13+ and SW13- subtypes have different oncogenic potential and convert with HDAC1 inhibition. Issue 1 (December 2016) - Davis, McKale; Daggett, Juliane; Pascual, Agnes; Lam, Jessica; Leyva, Kathryn; Cooper, Kimbal; Hull, Elizabeth
Abstract Background The BRM and BRG1 tumor suppressor genes are mutually exclusive ATPase subunits of the SWI/SNF chromatin remodeling complex. The human adrenal carcinoma SW13 cell line can switch between a subtype which expresses these subunits, SW13+, and one that expresses neither subunit, SW13-. Loss of BRM expression occurs post-transcriptionally and can be restored via histone deacetylase (HDAC) inhibition. However, most previously used HDAC inhibitors are toxic and broad-spectrum, providing little insight into the mechanism of the switch between subtypes. In this work, we explore the mechanisms of HDAC inhibition in promoting subtype switching and further characterize the oncogenic potential of the two epigenetically distinct SW13 subtypes. Methods SW13 subtype morphology, chemotaxis, growth rates, and gene expression were assessed by standard immunofluorescence, transwell, growth, and qPCR assays. Metastatic potential was measured by anchorage-independent growth and MMP activity. The efficacy of HDAC inhibitors in inducing subtype switching was determined by immunofluorescence and qPCR. Histone modifications were assessed by western blot. Results Treatment of SW13- cells with HDAC1 inhibitors most effectively promotes re-expression of BRM and VIM, characteristic of the SW13+ phenotype. During treatment, hyperacetylation of histone residues and hypertrimethylation of H3K4 is pronounced. Furthermore, histone modification enzymes, including HDACs and KDM5C, are differentially expressed during treatment but several features of this differential expression pattern differs from that seen in the SW13- and SW13+ subtypes. As the SW13- subtype is more proliferative while the SW13+ subtype is more metastatic, treatment with HDACi increases the metastatic potential of SW13 cells while restoring expression of the BRM tumor suppressor. Conclusions When compared to the SW13- subtype, SW13+ cells have restored BRM expression, increased metastatic capacity, and significantly different expression of a variety of chromatin remodeling factors including those involved with histone acetylation and methylation. These data are consistent with a multistep mechanism of SW13- to SW13+ conversion and subtype stabilization: histone hypermodification results in the altered expression of chromatin remodeling factors and chromatin epigenetic enzymes and the re-expression of BRM which results in restoration of SWI/SNF complex function and leads to changes in chromatin structure and gene expression that stabilize the SW13+ phenotype.